Kindheit, Kultur und moralische Emotionen zur Sozialisation von Furcht und Wut im ländlichen Madagaskar - Scheidecker, Gabriel 1982- (transcript-Verlag, 2017)
How do children in a Madagascan community learn to fear their parents, to regulate their anger, and enjoy themselves with friends? A cultural-anthropological contribution to emotional research
Description based on online resource; title from PDF title page (publisher's Web site, viewed June 01., 2017)
Keywords: Geschichte; Kulturanthropologe; Furcht; Gefühl; Erziehung; Kind; Sozialisation; Ländlicher Raum; Moralismus; Wut; Madagaskar; Anger; Childhood; Cultural Anthropology; Culture; Development; Eltern; Emotionen; Emotions; Entwicklung; Erziehungsideale; Erziehungspraktiken; Ethnologie; Ethnology; Kindheit; Kultur; Kulturanthropologie; Madagascar; Moralische Furcht; Parents; Social Psychology; Socialisation; Sozialpsychologie; Hochschulschrift